Teachers' Perceptions of Interactive Digital Media in Developing Young Children's Language Skills - Ghaisani Thifal Alkatiri; Isnaini Budi Hastuti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The use of interactive digital media has become one of the learning methods for children's language skills. This study aims to understand teachers' perceptions of the use of interactive digital media in early childhood language learning in early childhood education. Through a qualitative approach with a phenomenological design, this study explores teachers' views and experiences regarding the effectiveness of digital media and the challenges faced in its application. Data were obtained through interviews and observations of PAUD teachers at TPP Al Firdaus Surakarta, then analyzed using Miles and Huberman's interactive analysis technique. The results showed that teachers had a good understanding and positive attitude toward interactive digital media because it was considered capable of increasing children's participation, focus, and language skills through interesting and enjoyable activities. However, teachers also face obstacles in the form of limited facilities, internet connections, and the need for supervision to ensure that media use is not excessive. Therefore, improving teachers' digital literacy, providing supporting facilities, and cooperation between schools and parents are key to optimizing the use of interactive digital media in early childhood education.